Effects of sitagliptin beyond glycemic control: focus on quality of life - Sakamoto, Yoshiko (BioMed Central, 2013)
BACKGROUND: Recently, incretin hormones, including glucagon-like peptide-1 (GLP-1) analogue and dipeptidyl peptidase-4 (DPP-4) inhibitor, have been found to regulate glucose metabolism. The aim of this study was to elucidate the efficacy and safety of the clinical usage of DPP-4 inhibitors in Japan. METHODS: This study was designed as a prospective, open-label, multi-center trial. Patients with diabetes mellitus type 2 (T2DM) with poor glycemic profiles (HbA1c ≥ 6.2%) in spite of receiving a medical diet, therapeutic exercise, and/or medications were eligible for this study. The participants received 50 to 100 mg of the DPP-4 inhibitor sitagliptin once daily for 12 months. RESULTS: One hundred and eighty-eight subjects were enrolled. After 12 months of sitagliptin treatment, HbA1c levels decreased (7.65% ± 1.32% to 7.05% ± 1.10%, p < 0.001) as well as fasting plasma glucose (FPG) (145 ± 52 mg/dl to 129 ± 43 mg/dl, p = 0.005). The rate of glycemic control achieved (in accordance with the guidelines of the Japanese Diabetes Society) significantly increased. Blood pressure and serum levels of triglycerides and total cholesterol decreased significantly. Furthermore, the Pittsburgh Sleep Quality Index (PSQI) and Diabetes Symptomatic Scores improved significantly. Adverse events such as hypoglycemia and loss of consciousness occurred in twenty three subjects (11%). CONCLUSIONS: These results suggest that the actions of DPP-4 inhibitors improve not only glycemic control, but also blood pressure, lipid profiles, and quality of life (QOL). Sitagliptin is a sound agent for use in the comprehensive treatment of patients with T2DM.